Effects of physiotherapy during labor in a hospital in the amazon region: A pilot study (Research, Society and Development, 2021)
Objective: To evaluate the effects of physiotherapy on positive experiences with childbirth in a hospital in the eastern Amazon region. Method: Pilot, interventional, non-randomized study, with quantitative approach and descriptive and inferential analyses. Sociodemographic, economic, obstetric history and delivery variables were collected; The positive experience in childbirth was evaluated by the subscale of the questionnaire of experience and satisfaction with labor. Results: Participants were 43 parturients, allocated in an intervention group (GI) and control group (GC); both groups had moderate positive experience; the women who underwent physical therapy considered themselves a useful and cooperative member with the medical team that accompanied her; the primiparous women in GI were 80.9% and in GC 54.5%; it is observed that primiparous women were associated with the presence of laceration (RR: 2.05 [95% CI: 1.08; 3.91]; p = 0.007) and there was an association between lower urinary tract infection (UTI) and laceration (RR: 2.02; CI: 1.20; 3,39; p: = 0.003); women who suffered laceration had a longer labor time (laceration(+): 18.50 hours [95% CI: 11.33; 39.79]; laceration(-): 6.00 [95% CI: -5.052;  33,95]; U: 78.00; p = 0.013). Conclusion: The women who underwent physical therapy presented as a positive experience the fact that they considered themselves a useful and cooperative member with the medical team that accompanied her during childbirth. In addition, it is observed that primiparity was associated with laceration, which is increased along with the time of labor and presence of UTI.